Physics Didactic, Affect and Conceptualization - MARIA RITA OTERO; MARIA DE LOS ANGELES FANARO (Metaichmio Publications, 2011)
This paper discusses the relation between affects and conceptualization in physics didactics. We present a theoretical framework that has been used in an investigation about basic Quantum Mechanics teaching in the high school. The Path Integrals method of Feynman has been adopted as a Reference Conceptual Structure that is an alternative to the canonical formalism. The Proposed Conceptual Structure for Teaching is described and the conceptualization and its related affective aspects are analysed.